Valuation uncertainty, market sentiment and the informativeness of institutional trades - Yang, Lisa (Zongfei); Goh, Jeremy; Chiyachantana, Chiraphol (Journal of Banking & Finance, 2016)
Prior studies indicate that institutional investors are informed, in the sense that their trades predict price changes. In this study we show that return predictive ability of institutions arises (after controlling for size, book-to-market, and momentum) mainly from institutional sales of hard-to-value stocks during periods of positive market sentiment. These results support the notion that these stocks tend to be overvalued during periods of bullish market sentiment, and institutions contribute to market efficiency by identifying and trading on these overpriced stocks.